Amphioxus mouth after dorso-ventral inversion. Issue 1 (December 2016) - Kaji, Takao; Reimer, James; Morov, Arseniy; Kuratani, Shigeru; Yasui, Kinya
Abstract Introduction Deuterostomes (animals with 'secondary mouths') are generally accepted to develop the mouth independently of the blastopore. However, it remains largely unknown whether mouths are homologous among all deuterostome groups. Unlike other bilaterians, in amphioxus the mouth initially opens on the left lateral side. This peculiar morphology has not been fully explained in the evolutionary developmental context. We studied the developmental process of the amphioxus mouth to understand whether amphioxus acquired a new mouth, and if so, how it is related to or differs from mouths in other deuterostomes. Results The left first somite in amphioxus produces a coelomic vesicle between the epidermis and pharynx that plays a crucial role in the mouth opening. The vesicle develops in association with the amphioxus-specific Hatschek nephridium, and first opens into the pharynx and then into the exterior as a mouth. This asymmetrical development of the anterior-most somites depends on the Nodal-Pitx signaling unit, and the perturbation of laterality-determining Nodal signaling led to the disappearance of the vesicle, producing a symmetric pair of anterior-most somites that resulted in larvae lacking orobranchial structures. The vesicle expressedbmp2/4, as seen in ambulacrarian coelomic pore-canals, and the mouth did not open when Bmp2/4 signaling was blocked. Conclusions We conclude that the amphioxus mouth, which uniquely involves a mesodermal coelomic vesicle, shares its evolutionary origins with the ambulacrarian coelomic pore-canal. Our observations suggest that there are at least three types of mouths in deuterostomes, and that the new acquisition of chordate mouths was likely related to the dorso-ventral inversion that occurred in the last common ancestor of chordates.